Improving Women Entreprenurial Performance with Environmental Sustainability and Social Support - Ilhami, Susanti Dwi; Damayanti, Damayanti (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: The purpose of this study was to explore the role of environmental sustainability and social support in influencing agility towards women entrepreneurial performance of moslem women entrepreneur in Rembang Regency. Methodology: The data collection technique implemented was a questionnaire analyzed using SEM-PLS analysis. The sample size was 140 Muslim female entrepreneurs in Rembang Regency, particularly in SMEs. Result: The results showed that agility significantly effect women entrepreneurial performance and environmental sustainability. However, the role of environmental sustainability as a mediator and social support as a moderator was not proven. Conclusions: The moslem women entrepreneur can improve the entrepreneurial performance by using agility. Furthermore, Research indicate that agility can booster the environmental sustainability of women entrepreneur. Limitations: This study has a small number of variables, making it less comprehensive. Furthermore, the small number of respondents means the results cannot be generalized. Contribution: The high number of female entrepreneurs encourages further exploration of women business conditions. However, female entrepreneurs face obstacles and patriarchy, which discourages them from pursuing careers as entrepreneurs. Therefore, solutions are needed to achieve gender equality, especially for Muslim female entrepreneurs.